The Influence of Learning Outcomes Using the Entrepreneurship-Based of Project Based Learning (PJBL) Model: The Application to the First Grade (X class) of Senior High School Students in Mushroom Material - Nurul Jannah; Khairuna Khairuna (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS (JPBN), 2022)
The project based learning (PJBL) model is defined as an innovative model that is critically multistrategic basically for understudy progress in creating current 21 century abilities. The purpose of the study was to determine the influence of student learning outcomes on mushroom material by applying an entrepreneurship-based learning model (PJBL) first grade (X class) of Senior High School SMA Negeri 1 Aek Songsongan for the 2021/2022 academic year. Type of research with quantitative by True-ekperimental with the from of pre-test post-test control group design. Review test comprised of experimental class X MIA3 and control class X MIA4 Â selected by cluster random sampling. The research instrument uses diagnostic tests through multiple choice tests and student response questionnaires. Data analysis methods utilizing the assistance of IBM SPSS 24 and Microsoft Excel 2013. The calculation of the hypothesis test results, based on the significance level of Î±= 0.05 obtained a tcount 6,830 and a ttable value of 1,669. Cause tcount > ttabel, then H0 is dismissed and Ha is acknowledged. Then it can be interpreted by this, is a significant influence of the entrepreneurship based project based learning (PJBL) learning model on the learning outcomes of class X students on Mushroom material. With a typical score got by the control class of 45.15 and experimental class of 62.52 with the achievement of the maximum score of the control class 60 and the experimental class 83. Â Â